Effects of pneumoperitoneum with carbon dioxide and helium on renal function and morphology in rats - Freitas,Pedro Felipe Silva de (2013)
PURPOSE: To evaluate the effects of pneumoperitoneum with carbon dioxide and helium on renal function and morphology in a rat model. METHODS: Twenty four rats were randomized into three groups (n=8): gasless insufflation ('open', Pressure=0 mmHg), carbon dioxide pneumoperitoneum at 12 mmHg, and helium pneumoperitoneum at 12 mmHg; all lasting 90 minutes.. A cystostomy was performed and the bladder was emptied. At the end of the experiment, the urine produced, a blood sample and the left kidney of each animal were collected. The following variables were obtained: serum sodium, potassium, urea and creatinine, urine volume and creatinine. The creatinine clearance was estimated for each animal. The kidneys were stained with hematoxylin and eosin (HE) and evaluated by a pathologist blinded to the groups. RESULTS: The CO2 and Helium groups did not differ in the variables evaluated. Both developed oliguria (p<0.001 vs. gasless). The CO2 group presented hyperkalemia compared to gasless (p=0.05), which did not attain significance in the helium group. Histopathological analysis revealed mild hydropic degeneration and congestion in the three groups, with no significant difference among them. CONCLUSIONS: The type of gas resulted in no difference in the variables of renal function and morphology assessed. The increase in serum potassium was only observed with CO2 insufflation suggests a combined effect of elevated intra-abdominal pressure and metabolic effects of pneumoperitoneum.